2021
DOI: 10.1108/cms-08-2021-0333
|View full text |Cite
|
Sign up to set email alerts
|

The role of project managers’ attributes in project sustainability management and project performance under China-Pakistan economic corridor

Abstract: Purpose Steered by upper echelon theory, this study aims to scrutinize the prevalence of project manager demographic factors (age, education and experience) in project sustainability management and project performance. Design/methodology/approach We used a sample of 209 project managers/supervisor/team leaders who were working in the projects of the China-Pakistan Economic Corridor (CPEC). Findings The results indicate that project manager demographic factors have a significant influence on project perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 83 publications
1
16
1
Order By: Relevance
“…In the currently turbulent environment, society demands a sustainable environment (Larbi-Siaw et al, 2022). Based on this concept, society expects the senior management of enterprises to act more socially responsibly and contribute more to society than to the company itself (Hashim et al, 2021).…”
Section: The Moderating Role Of Managerial Attributesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the currently turbulent environment, society demands a sustainable environment (Larbi-Siaw et al, 2022). Based on this concept, society expects the senior management of enterprises to act more socially responsibly and contribute more to society than to the company itself (Hashim et al, 2021).…”
Section: The Moderating Role Of Managerial Attributesmentioning
confidence: 99%
“…However, in our study, we use age, education, and experience as managerial demographic factors in the context of UE theory that influence sustainability practices in SMEs. For instance, Hashim et al (2021) state that older managers desire more environmental practices, while Elmagrhi et al (2019) show that younger managers are more environmentally oriented. Similarly, some studies have demonstrated that highly educated managers are actively engaged in social and environmental activities (Hashim et al, 2021; Quazi, 2003; Tran & Pham, 2020), while others have found insignificant links between education and sustainability activities (Yildiz Çankaya & Sezen, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…An experienced manager is more capable of adopting different approaches than a naive manager to reach the desired goals. For instance, the project manager"s experience has been established to be a good predictor of project success, efficiency and sustainability in project management domains (Hashim et al, 2021). A manager with more years of service is also more likely to be sensitive towards their team and may be well aware of the currencies attached to the performance of the team members.…”
Section: The Moderating Role Of Rater's Experiencementioning
confidence: 99%